2016
DOI: 10.1007/s00415-016-8287-9
|View full text |Cite
|
Sign up to set email alerts
|

External validation of a 3-step falls prediction model in mild Parkinson’s disease

Abstract: The 3-step falls prediction model (3-step model) that include history of falls, history of freezing of gait and comfortable gait speed <1.1 m/s was suggested as a clinical fall prediction tool in Parkinson’s disease (PD). We aimed to externally validate this model as well as to explore the value of additional predictors in 138 individuals with relatively mild PD. We found the discriminative ability of the 3-step model in identifying fallers to be comparable to previously studies [area under curve (AUC), 0.74; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 43 publications
2
38
2
2
Order By: Relevance
“…It is also noteworthy that trial 1 values and mean (trials 1 and 2) values of both static and dynamic start identified 1.1 m/s as an optimal cut-off point. This finding is in line with the suggested cut-off point for comfortable gait speed as a predictor in the 3-step model [2, 3]. However, while the 3-step model prescribes the use of the mean of two trials, our observations suggest that a single trial with static start will suffice.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…It is also noteworthy that trial 1 values and mean (trials 1 and 2) values of both static and dynamic start identified 1.1 m/s as an optimal cut-off point. This finding is in line with the suggested cut-off point for comfortable gait speed as a predictor in the 3-step model [2, 3]. However, while the 3-step model prescribes the use of the mean of two trials, our observations suggest that a single trial with static start will suffice.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, comfortable gait speed < 1.1 m per second (m/s) has been suggested as an important predictor of future falls in PD [25]. However, there are different standardizations for the conduct of the 10MWT, for example, measuring over different distances (10 or 6 m) and the inclusion or exclusion of an acceleration distance, i.e., dynamic vs. static start [13, 6]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 • Nutt Retropulsion Test (NRT) as a test of reactive balance responses (retropulsion) due to unexpected shoulder pull (score range 0-3). Those scoring ≥1 were categorized as having an abnormal TG performance.…”
Section: Procedures and Instrumentsmentioning
confidence: 99%
“…7 To follow previous findings and approaches, 11 individuals with global cognitive impairment were excluded from the development sample. 7 To follow previous findings and approaches, 11 individuals with global cognitive impairment were excluded from the development sample.…”
Section: Introductionmentioning
confidence: 99%